The Role of Virtual Try-On (VTO) as a Technological Stimulus in Optimizing Online Shopping Experience (OSE) and Purchase Decisions - Mimanda, Arika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid growth of e-commerce is driving the need for more immersive shopping experiences, particularly in visual-dependent product categories such as cosmetics and fashion. Sensory gaps in online shopping often increase risk perception and decrease consumer confidence in decision-making (Scholz & Duffy, 2018). This conceptual study aims to propose the strategic role of Artificial Intelligence-based Virtual Try-On (VTO) as a technological stimulus within the Stimulus Organism Response (SOR) framework. The review was conducted through a Descriptive Conceptual Review using a theoretical thematic synthesis that integrates key literature on virtual realism, technological utility, and functional risk reduction (Kim & Forsythe, 2008; Poushneh & Vasquez-Parraga, 2017). The results of the synthesis indicate that VTO systematically strengthens the cognitive and affective dimensions of the Online Shopping Experience (OSE) by increasing information clarity, interaction enjoyment, and confidence in product suitability (Javornik, 2016; Izogo & Jayawardhena, 2018). This improvement in OSE quality serves as an organismal mechanism that plays a crucial role in driving behavioral responses, namely purchasing decisions. This study confirms that VTO integration in e-commerce is not merely a visual innovation, but a strategic experiential driver capable of optimizing the overall consumer journey. These theoretical findings provide the conceptual foundation necessary for further empirical testing of the causal relationships between VTO, OSE, and purchasing decisions, as well as their strategic implications for digital marketing managers.